Design estratégico e Scrum: suas relações para processos de projeto de websites em agências de comunicação - Carapeto, João Luiz Xavier (Universidade do Vale do Rio dos Sinos, 2012)
This work presents a research whose objective consisted in evaluating the link possibilities between the Strategic Design and Scrum for creation and development of websites by communication agencies. In order to do so, a path was taken that presented definitions regarding the concept of Strategic Design and characteristics of the Metaproject phase and Scrum methodology and establishing points of contact between them. Furthermore, additional definitions about websites were also presented. The research was outlined by a qualitative exploratory study, composed of two separate case studies. The first took place in a workshop environment and had the intention to observe how the concepts from Strategic Design could influence the creation of new products for communications agencies. The second case study took place inside the 3YZ communication agency, while developing a Hotsite and had the intention to observe the dynamics that occur with the application of concepts and techniques of Scrum. The research shows that the application of concepts and techniques of Strategic Design and Scrum can influence the creation and development of websites for communication agencies especially with the use of the metaprojectual phase in order not only to increase the number of participants in the creation of ideas but also the sense of relevance from the staff towards the project, and with limitations on the creation of systemproducts and in the impossibility of conducting cyclical deliveries of functional product parts, opening, therefore, possibilities – also presented as an initial version for a web development project – to continue this research and explore its potentials and overcome its limitations.
Keywords: Design estratégico; Scrum; Website; Método; Strategic design; Method; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial